Algorithms and data structures : with applications to graphics and geometry - Nievergelt, Jurg; Hinrichs, Klaus; BC Open Textbook Project; BCcampus (Global Text, 2011)
"This is a textbook for first year Computer Science. Algorithms and Data Structures With Applications to Graphics and Geometry."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Algorithms -- Textbooks; Data structures (Computer science) -- Textbooks; Electronic books